MO750THE COMBINED PROGNOSTIC SIGNIFICANCE OF ALKALINE PHOSPHATASE AND INTRA-CRANIAL ARTERIAL CALCIFICATIONS IN HEMODIALYSIS PATIENTS. (29th May 2021) - Cohen Hagai, Keren; Erez, Daniel; Zitman-Gal, Tali; Fanadka, Feda; Einbinder, Yael; Benchetrit, Sydney
Abstract: Background and Aims: Intra-cranial arterial calcification (ICAC) in hemodialysis (HD) patients has a prevalence of about 90%, and its severity is correlated with age, hemodialysis vintage and mineral bone disease. Elevated concentrations of calcium and phosphorus are not sufficient to induce medial calcification because of inhibition by pyrophosphate. Alkaline Phosphatase (ALP) promotes vascular calcification by hydrolyzing pyrophosphate. Epigenetic mechanisms regulation by Apabetalone downregulates pathways involved in vascular calcification. This study assessed the combined impact of ICAC and elevated serum ALP on mortality among chronic HD patients. Method: vascular calcifications represented by ICAC were measured simultaneous with mineral bone disease parameters including serum ALP of chronic HD patients who underwent non-contrast brain computerized tomography (CT) from 2015 to 2018 in our institution. Results: This retrospective study included 153 hemodialysis patients (mean age 71.3±12.1 years, 60.1% male). Of the total cohort, 12(7.8%) had no brain calcifications and 69 (45.1%) had multiple intracranial calcifications. Considering the patients with normal ALP and no calcification as the reference group yielded adjusted odds ratios for all-cause mortality of 4.6 (95%CI 1.7-12.7) among patients with brain calcifications and normal ALP, p=0.003, and odds ratios for all-cause mortality of 6.1 (95%CI 2.1-17.7) among patients with brain calcifications and increased ALP. Conclusion: We founded an independent association between ICAC and the risk of death among hemodialysis patients. The combined effect of ICAC and increased ALP was significantly associated with higher odds-ratio for all-cause mortality in chronic HD patients and may contribute to the risk stratification of these patients.